Analysis of factors affecting information-seeking behaviour of the Ministry of Administrative and Bureaucratic Reform’s policy analysts - Nur Sanny Rahmawati; Laksmi Laksmi; Rahmi Rahmi (Berkala Ilmu Perpustakaan dan Informasi, 2023)
Introduction. This study examines the effect of job descriptions and capability specifications on the information seeking behaviour patterns of policy analysts at the Ministry of Administrative and Bureaucratic Reform. Data Collection Methods. Data was gathered via questionnaires. The respondents were 118 policy analysts across beginner, intermediate, and advanced levels. Data Analysis. Research data were analysed using PLS-SEM. Results and Discussion. The study reveals that the job descriptions had a positive impact on the policy analysts’ information-seeking habits at the Ministry of Administrative and Bureaucratic Reform. However, the capability specifications did not show any substantial positive effect. Conclusion. The research concludes that job descriptions play a crucial role in shaping the information-seeking behaviour of policy analysts, whereas the impact of capability specifications remains insignificant. The study further suggests several stakeholders responsible for managing information, like libraries, should take an active role in handling the data produced by policy analysts from various units. This would help the sustainable use of such data in the creation of public policies.